Pengaruh Pengembangan Objek Wisata dan Tingkat Kunjungan Wisatawan Terhadap Pertumbuhan Ekonomi Masyarakat - Muhammad Amin; Yuslan Idrus; Diana Puturuhu (Univiversitas Dr. Djar Wattiheluw, 2023)
This study aims to analyze the impact of the development of tourist objects and tourist visits on the community's economy (a study on the Kuako beach tourism object, Soahuku Village, Amahau District, Central Maluku Regency, Maluku Province). Data collection was carried out through observation, interviews and questionnaires. The population in the study were all people around the Kuako beach and tourists visiting the Kuako beach during the period July 2022 to February 2023. The sample was drawn using a purposive sampling method with a final sample of 71 respondents. Research data were analyzed using multiple linear regression analysis. The results of the study show that the development of tourist objects and the level of tourist visits have a positive and significant impact on the people's economy.